Penetration and infectivity of entomopathogenic nematodes against Lema sp. (Chrysomelidae: Coleoptera) infesting turmeric (Curcuma longa L.) and their multiplication - S Devasahayam, S J Eapen, R Pervez, T K Jacob, (Journal of Spices and Aromatic Crops, 2014)
Penetration and infectivity of eight native isolates of entomopathogenic nematodes (EPNs), Heterorhabditis sp. (IISR-EPN 01); Steinernema sp. (IISR-EPN 02); S. ramanai (IISR-EPN 03); S. carpocapsae (IISR-EPN 06), Oscheius gingeri (IISR-EPN 07) and Oscheius spp. (IISR-EPN 04, 05 and 08) were evaluated against larvae of leaf feeder (LF) Lema sp. infesting turmeric. Among the tested EPNs, Steinernema sp. (IISR-EPN 02) and O. gingeri (IISR-EPN 07) were more pathogenic to LF larva as they brought about 100% mortality to the insect within 48 h post exposure, followed by Heterorhabditis sp. (IISR-EPN 01) and Oscheius sp. (IISR-EPN 08) after 72 h of exposure. S. ramanai (IISR-EPN 03) and Oscheius spp. (IISR-EPN 04 and 05) took 96 and 120 h, respectively, to kill the test insect. Lema sp. larva was the most suitable host for multiplication of infective juveniles (IJs) of O. gingeri (IISR-EPN 07), which yielded 11, 480 IJs larva-1, followed by Steinernema sp. (IISREPN 02) (8, 658 IJs larva-1) and S. carpocapsae (IISR-EPN 06) (6, 810 IJs larva-1), however, Heterorhabditis sp. (IISR-EPN 01) less multiplied. The maximum number of Steinernema sp. (IISREPN 02) IJs penetrated into test larva (17.5 IJs larva-1), followed by S. carpocapsae (IISR-EPN 06) (10.2 IJs larva-1) and the fewest (2.8 IJs larva-1) were of Oscheius sp. (IISR-EPN 08). The infectivity of the above EPNs against LF is being reported for the first time which opens up a new hope of utilizing them in insect pest management in turmeric.